2019
DOI: 10.1155/2019/7645106
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Knowledge, Testing, and Vaccination History among Undergraduate Public Health Students in Ghana

Abstract: Background. Hepatitis B virus (HBV) infection is a serious public health problem in many parts of the world. The risk of acquiring the infection through exposure to blood, semen, and other bodily fluids is highest among health care workers (HCW) including trainees. Ghana is considered a high risk country for HBV; however little is known about the knowledge and prevention practices of the infection in the country. This study assessed the knowledge, testing, and vaccination history of HBV and their related facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
28
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 24 publications
11
28
3
Order By: Relevance
“…This could have impacted on their hepatitis B screening rates. These ndings are in agreement with those of Osei, Niyilapah (40) which indicated that females were more likely to screen for hepatitis B compared to males. In addition, males often show a reluctancy in receiving health care services which could explain their low screening rates for hepatitis B (41,42).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This could have impacted on their hepatitis B screening rates. These ndings are in agreement with those of Osei, Niyilapah (40) which indicated that females were more likely to screen for hepatitis B compared to males. In addition, males often show a reluctancy in receiving health care services which could explain their low screening rates for hepatitis B (41,42).…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, these may have been motivated to take all the vaccine doses. A number of studies have concluded that an adequate level of knowledge on disease conditions increases the uptake of prevention services such as hepatitis B vaccination (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies from Ghana and India described moderate and fair knowledge about HBV infection among medical and pharmacy students, respectively. [ 22 23 ] A low level of knowledge and awareness among medical, dental, and pharmacy students might be due to their unstructured curriculum design and less exposure to tutorials and assignments related to infectious diseases on a regular basis. The overall mean knowledge scores of the students were found as good as previous studies[ 16 22 23 24 ] but higher than one Indian study[ 4 ] with a significant ( P < 0.001) difference in the knowledge mean scores between medical and pharmacy students in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 23 ] A low level of knowledge and awareness among medical, dental, and pharmacy students might be due to their unstructured curriculum design and less exposure to tutorials and assignments related to infectious diseases on a regular basis. The overall mean knowledge scores of the students were found as good as previous studies[ 16 22 23 24 ] but higher than one Indian study[ 4 ] with a significant ( P < 0.001) difference in the knowledge mean scores between medical and pharmacy students in the present study. [ 8 ] The difference in mean knowledge scores between medical and pharmacy students might be due to more in-depth discussion on infectious diseases with medical students during their lectures, tutorials, and clinical exposures compared to pharmacy students.…”
Section: Discussionmentioning
confidence: 99%
“…Good knowledge was de ned by answering ≥ 70% of the knowledge questions correctly, whereas poor knowledge was de ned as < 70% of correct answers. The attitude score was calculated by summing the marks of questions (20)(21)(22). Positive attitude was de ned by answering ≥ 70% of the attitude items correctly, whereas negative attitude was indicated by < 70% of correct answers.…”
Section: Methodsmentioning
confidence: 99%